2022
DOI: 10.3390/rs14030694
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Phragmites australis Aboveground Biomass in the Momoge Wetland Ramsar Site Based on Sentinel-1/2 Images

Abstract: Phragmites australis (P. australis) is one of the most important plant species found in wetland ecosystems, and its aboveground biomass (AGB) is a key indicator for assessing the quality or health of a wetland site. In this study, we combined Sentinel-1/2 images and field observation data collected in 2020, to delineate the distribution of P. australis in the Momoge Ramsar Wetland site by using a random forest method, and further, to estimate AGB by comparing multiple linear regression models. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The Tao’er and Erlongtao Rivers flow through the area. The plant and animal resources in the reserve are rich, with more than 600 species of seed plants, including herbaceous species such as reeds, small-leafed adults, moss grasses, and fragrant cattails, which have a high population density and biomass, are the dominant species in the reserve, and are distributed in slightly different areas ( Zhao et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Tao’er and Erlongtao Rivers flow through the area. The plant and animal resources in the reserve are rich, with more than 600 species of seed plants, including herbaceous species such as reeds, small-leafed adults, moss grasses, and fragrant cattails, which have a high population density and biomass, are the dominant species in the reserve, and are distributed in slightly different areas ( Zhao et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies revealed that backscatter coefficients of SAR were crucial for AGB retrieval [13,17]. Difference (VH − VV), sum (VH + VV), and radar texture information are also significant in AGB retrieval [17,[46][47][48]. Hence, we obtained radar backscatter coefficients, differences (VH − VV), sums (VH + VV), and radar texture information from S-1.…”
Section: Obtainment Of Relevant Variablesmentioning
confidence: 99%
“…Some variables have a low correlation with AGB, or these variables may be co-dependent. To overcome the challenge of selecting the fewest predictors with the best predictive power and to help in the interpretation of the final model, backward feature elimination (BFE) was used to select appropriate variables [47,52]. Variables used in 16 AGB models are shown in Table 3.…”
Section: Selection Of Variables Used In Agb Modelingmentioning
confidence: 99%
“…Tian et al [16] used random forest to classify the vegetation of wetlands in arid areas of Xinjiang. L. F. Ruiz et al [17][18][19][20][21] used Sentinel-1 images to classify wetland types.…”
Section: Introductionmentioning
confidence: 99%